Business networking relationships for business success - S. De Klerk; J. Kroon (South African Journal of Business Management, 2008)
This study explored the context of business relationships in the networking practices of South African businesses. The objective of this study was to investigate the networking practices of Gauteng businesses and specific perceptions and experiences of business owners and managers on their business networking objectives. A multi-method design was used, which included qualitative research (focus groups) and quantitative research (structured questionnaire). Perceptions recorded amongst the participants indicated that business relationships are built for referrals and strategic networking connections. Different forms of business networking and different motivations behind the building of business networks were identified, such as profit, access to resources and improved efficiency. Different characteristics in terms of business relationships were identified and different age groups, group 1 (44 years and younger) and group 2 (older than 45 years of age) indicated that they felt differently about the number of connections in a network. This article can contribute to the business practice of networking and the awareness of business owners and managers in terms of the importance and influence of networking in their specific business.